The tropics bite back : culinary coups in Caribbean literature - Loichot, Valérie, 1968- (University of Minnesota Press, 2013)
The ubiquitous presence of food and hunger in Caribbean writing - from folktales, fiction, and poetry to political and historical treatises - signals the traumas that have marked the Caribbean from the Middle Passage to the twenty-first century. This book traces the evolution of the Caribbean response to the colonial gaze (or, rather, the colonial mouth) from the late nineteenth century to the twenty-first. Unlike previous scholars, the author does not read food simply as a cultural trope. Instead, she is interested in literary cannibalism, which she interprets in parallel with theories of relation and creolization.